Anti-sticking agent, preparation method thereof and application of anti-sticking agent to vinyl polymerization reaction kettle

By combining modified polyaniline solution and cosolvent, an anti-sticking kettle agent for vinyl polymerization reactor was prepared, which solved the problem of polymer bonding, improved production efficiency and reduced environmental pollution and cost.

CN119192987AInactive Publication Date: 2024-12-27TIANJIN SUNNYMER +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411721506.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the vinyl polymer manufacturing process, the polymer is prone to bond to the reactor wall and other surfaces, resulting in an increase in the cleaning time and a decrease in product quality. The existing anti-sticking agents have problems of environmental pollution and high costs.

Method used

A modified polyaniline solution is used as the basis, combined with a co-solvent and a film-forming agent, and adjusted the pH value, an environmentally friendly aqueous solution anti-stick kettle agent is prepared for vinyl polymerization reactor to prevent bonding.

Benefits of technology

It effectively prevents the bonding of polymers on the reactor wall, reduces the time of cleaning the kettle and the number of "fish eyes", improves production efficiency, and avoids environmental pollution and cost increase.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of high polymer application, and particularly relates to an anti-sticking agent, a preparation method of the anti-sticking agent and application of the anti-sticking agent to a vinyl polymerization reaction kettle. The anti-sticking agent comprises the following components in percentage by mass: 1.5-35% of a modified polyaniline solution, 0.5-8% of a film-forming agent and the balance of water. According to the anti-sticking agent for the kettle, the modified polyaniline is used as a basic raw material, the modified polyaniline keeps excellent electrical properties and has the characteristic of inhibiting polymerization of a contact surface, and then an environment-friendly aqueous solution is prepared by adding the film-forming agent and adjusting the pH value, so that an efficient anti-sticking effect can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high polymer application, and particularly relates to an anti-sticking kettle agent and a preparation method thereof and application thereof in a vinyl polymerization reaction kettle. Background Art

[0002] Polyaniline is a widely and intensively studied polymer, and different industrial applications have been developed due to the fact that its electronic and optical properties can be modified by changing the number of protons, electrons, or both.

[0003] Polyaniline usually exists in the form of a mixture, and the y value is usually used to represent the degree of redox of polyaniline; when 0≤y≤1, the oxidation state of the polymer increases as the y value decreases. When y=1, it is completely reduced polyaniline (also called emeraldine); when y=0, it is completely oxidized polyaniline (also called polyphenylenediamine); when y=0.5, it is partially oxidized and partially reduced polyphenylenediamine (also called emeraldine). Each oxidation state can exist in its base form or in its protonated form by treating the base with an acid.

[0004] In the process of manufacturing vinyl polymers, there is a common phenomenon that polymers stick to the reactor wall, stirring, baffle and other surfaces (industry called sticking), which is one of the difficult problems in industrial production, especially in the production of polyvinyl chloride resin, where vinyl chloride monomer is polymerized to form polyvinyl chloride resin (PVC). Due to the presence of initiators, free radicals are formed, which initiate the polymerization of vinyl chloride monomer, continuously forming chain growth, and causing polyvinyl chloride resin to precipitate from the suspension system. The above-mentioned polymerization process is carried out in a polymerization reactor, and there will inevitably be polymers sticking to the reactor wall, which requires increasing the time for cleaning the reactor. More importantly, these stickings will enter the next polymerization cycle, which will increase the number of "fish eyes" of PVC resin and affect the resin quality. In addition, increasing the cleaning time is very unfavorable to increase production.

[0005] To solve the above problems, China has introduced related anti-sticking kettle coating technologies while introducing polyvinyl chloride polymerization technology. The most common product is polyresorcinol, which is a solid product that must be dissolved in sodium hydroxide aqueous solution before use. After use, the brown sewage formed needs to be discharged, which is not conducive to environmental protection. The improved anti-sticking kettle agent on the market is a mixture of phenolic resins. Although the anti-sticking kettle effect is good, the product needs nitrogen protection (it is easy to oxidize and reduce the anti-sticking kettle effect), and it cannot be diluted with water to increase the cost. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an anti-sticking kettle agent and a preparation method thereof and application thereof in a vinyl polymerization reactor.

[0007] To achieve the above object, the technical solution adopted by the present invention is: An anti-sticking kettle agent comprises the following components by weight: 1.5%-35% of a modified polyaniline solution, 0.5%-8% of a film-forming agent and the balance of water.

[0008] Preferably, the following components are included: The modified polyaniline solution comprises modified polyaniline and a cosolvent; the mass content of the modified polyaniline solution is 10-40%.

[0009] The modified polyaniline is sulfonated polyaniline or deprotonated polypropylamine; The sulfonated polyaniline is obtained by sulfonating polyaniline; the molecular weight of the polyaniline is 80,000-150,000, y=0.35-0.7; the y value represents the degree of redox of the polyaniline; The deprotonated polyaniline is obtained by dehydrogenating polyaniline; the molecular weight of the polyaniline is 80,000-150,000, y=0; and the y value represents the redox degree of the polyaniline.

[0010] The sulfonated polyaniline is prepared by the following steps: adding polyaniline to a sulfonating agent, controlling the reaction temperature at 10-35°C, and reacting for 2-5 hours; the sulfonating agent is fuming sulfuric acid, a 98% or more sulfuric acid aqueous solution, or sulfur trioxide; The deprotonated polyaniline is prepared by the following steps: immersing the polyaniline in an alkaline solution, mixing for 40-60 minutes, filtering to obtain a precipitate, and washing to obtain the deprotonated polyaniline.

[0011] The auxiliary solvent is one of dimethyl sulfoxide, N-methyl-2-pyrrolidone, tetrahydrofuran, formic acid, acetic acid, or dimethylformamide or a mixture thereof; and the film-forming agent is polyvinyl alcohol.

[0012] The anti-sticking kettle agent has a viscosity of 3.0-12.0 mPa.s and a pH of ≥12.0.

[0013] The present invention also includes a method for preparing the anti-sticking agent, comprising the following steps: adding deionized water into a mixing container, starting stirring, adding a modified polyaniline solution and a film-forming agent; then adding an alkali solution to adjust the pH to ≥ 12.0, and continuing to fully mix to obtain the anti-sticking agent finished product.

[0014] The present invention also includes an application of the anti-sticking kettle agent, which is applied to a vinyl polymerization reaction kettle.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The anti-sticking agent of the present application uses modified polyaniline as the basic raw material. The modified polyaniline maintains excellent electrical properties and has the characteristic of inhibiting contact surface polymerization. Then, by adding a film-forming agent and adjusting the pH value, it is prepared into an environmentally friendly aqueous solution, which can achieve efficient anti-sticking effect. The special electrochemical properties of the modified polymer can be used for the polymerization of various vinyl monomers, including suspension polymerization, micro-suspension polymerization, bulk polymerization and solution polymerization. DETAILED DESCRIPTION

[0016] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments. Example 1

[0017] Modified polyaniline is sulfonated modified polyaniline to prepare anti-sticking agent: 1. Prepare sulfonated modified polyaniline; add polyaniline to a sulfonating agent, control the reaction temperature to 10-35°C, and react for 2-5 hours; the sulfonating agent is fuming sulfuric acid, 98% or more sulfuric acid aqueous solution or sulfur trioxide; the molecular weight of the raw material polyaniline is 80,000-150,000, y=0.35-0.7; the y value represents the degree of redox of the polyaniline; the raw material polyaniline is not limited by the technical source, and can be a polyaniline obtained by a polymerization method well known to those skilled in the art, such as: chemical oxidation method, solution polymerization method, emulsion polymerization method, microemulsion polymerization method or electrochemical polymerization method; this embodiment is exemplified by polyaniline with y=0.35-0.7 manufactured by commercial emulsion polymerization method and a degree of polymerization of 12500.

[0018] In this embodiment, the sulfonating agent is fuming sulfuric acid as an example, and the following steps are specifically used: In a glass stirring reaction bottle, 15 grams of polyaniline is dissolved in 400 milliliters of fuming sulfuric acid (H2SO4·SO3) under continuous stirring at room temperature to carry out sulfonation reaction. During the sulfonation period, the color of the solution changes from dark purple to dark blue. The solution is slowly added to 2000 milliliters of methanol for precipitation within 20 minutes, and then 1000 milliliters of acetone with less polarity is added to increase precipitation. Then filter. Wash the precipitate cake with methanol in batches until the pH value of the filtrate is 7. The precipitate is dried to obtain sulfonated polyaniline.

[0019] 2. Prepare a modified polyaniline solution; slowly add 23 g of sulfonated modified polyaniline into 100 g of a co-solvent, wherein the co-solvent is a mixture of 50 g of N-methyl-2-pyrrolidone and 50 g of formic acid; start stirring and mixing for 2.0 hours, and end the mixing when the solution completely turns dark blue, thereby obtaining a modified polyaniline solution as the basic material of an anti-sticking agent.

[0020] 3. Prepare an anti-sticking agent; add 2000 ml of deionized water to a stirring mixing container, start stirring, add 30 g of the modified polyaniline solution, and continue to add 10 g of a film-forming agent (the film-forming agent is: polyvinyl alcohol with a degree of alcoholysis of 99.5-99.9 mole%, and a degree of polymerization of 1350-1550, and the polyvinyl alcohol is prepared to have a solid content of 5.0%), and then use 12 g of a 5% sodium hydroxide aqueous solution to adjust the pH value to 12.3, continue to mix thoroughly, and test the viscosity of the aqueous solution to be 4.3 mPa.s, thereby obtaining the anti-sticking agent of the present invention. Example 2

[0021] Modified polyaniline is sulfonated modified polyaniline to prepare anti-sticking agent: 1. Prepare sulfonated modified polyaniline; purchase commercially available sulfonated modified basic raw material polyaniline, which is not limited by the technical source and can be polyaniline obtained by a polymerization method well known to those skilled in the art, such as chemical oxidation, solution polymerization, emulsion polymerization, microemulsion polymerization or electrochemical polymerization; in this embodiment, polyaniline with y=0.35-0.7 manufactured by emulsion polymerization and a degree of polymerization of 12500 is purchased.

[0022] The raw material for the sulfonation reaction is sulfur dioxide (SO3). The commercially available polyaniline is exposed to SO3 gas for a time and temperature within a predetermined range. Gas-phase sulfonation of polyaniline at high temperatures can shorten the reaction time, while using low temperatures will increase the reaction time. In the case of excess SO3 gas, gasification can be completed in about 12 hours at room temperature.

[0023] The implementation method adopted in this embodiment is as follows: 2g of the above polyaniline is added to an empty glass reactor, 400ml of 23% fuming sulfuric acid is continuously introduced, the reaction temperature is controlled at 30-45°C, and the reaction is completed in 8 hours. The obtained compound is the sulfonated modified polyaniline of the present invention.

[0024] 2. Prepare an anti-sticking agent; slowly add 2.0 g of sulfonated modified polyaniline into 20 g of a co-solvent, wherein the co-solvent is N-methyl-2-pyrrolidone; start stirring and mixing for 2.0 hours, and end the mixing when the solution completely turns dark blue, thereby obtaining modified polyaniline as the basic material of the anti-sticking agent.

[0025] 3. Prepare an anti-sticking agent; add 200 ml of deionized water to a 1000 ml stirring mixing container, start stirring, add 10 g of the modified polyaniline solution, and continue to add 3 g of a film-forming agent (the film-forming agent is: polyvinyl alcohol with a degree of alcoholysis of 99.5-99.9 mole% and a degree of polymerization of 1350-1550, and the polyvinyl alcohol is prepared to have a solid content of 5.0%), and then use 7 g of 8% ammonium hydroxide aqueous solution to adjust the pH value to 12.5, continue to mix thoroughly, and test the viscosity of the aqueous solution to be 3.7 mPa.s, thereby obtaining the anti-sticking agent of the present invention. Example 3

[0026] Deprotonation (dehydrogenation) modified polyaniline to prepare anti-sticking agent: 1. Preparation of deprotonated polyaniline; the deprotonated polyaniline is obtained by dehydrogenation of polyaniline; the molecular weight of the polyaniline is 80,000-150,000, y=0; the y value represents the degree of redox of the polyaniline. The raw material polyaniline is not limited by the technical source, and can be polyaniline obtained by a polymerization method well known to those skilled in the art, such as chemical oxidation, solution polymerization, emulsion polymerization, microemulsion polymerization or electrochemical polymerization; this embodiment uses commercially available emulsion polymerization to produce polyaniline with y=0 and a degree of polymerization of 13200 for exemplary description.

[0027] Specifically, the following steps are adopted: the raw material polyaniline is washed with 500 ml of distilled water to remove the residual acid, and then 2000 ml of 1M ammonium hydroxide is added, stirring is started for 45 minutes, and the precipitate is filtered and washed. The color of the polyaniline changes from dark blue-green to copper brown, and the deprotonated polyaniline of the present invention is obtained.

[0028] 2. Prepare a modified polyaniline solution; slowly add 20 g of deprotonated polyaniline into 50 ml of tetrahydrofuran solution, start stirring, and the solution color turns dark blue and completely dissolves to obtain a modified polyaniline solution.

[0029] 3. Prepare an anti-sticking agent; add 20g of the above polyaniline solution into a 2000ml beaker, add 100ml of distilled water, start stirring, and continue to add 6g of a film-forming agent (the film-forming agent is: polyvinyl alcohol with a degree of alcoholysis of 99.5-99.9 mole% and a degree of polymerization of 1350-1550, and the polyvinyl alcohol is prepared to have a solid content of 5.0%), stir for 1 hour, and then use 4.2g of a 5% sodium hydroxide aqueous solution to adjust the pH value to 12.1, continue to mix thoroughly, and test the viscosity of the aqueous solution to be 4.2mPa.s, thereby obtaining the anti-sticking agent of the present invention. Example 4

[0030] Deprotonation (dehydrogenation) modified polyaniline to prepare anti-sticking agent:

[0031] 1. Preparation of deprotonated polyaniline: Deprotonated (dehydrogenated) modified polyaniline uses the commercially available polyaniline with y=0 and a degree of polymerization of 13200 as a basic raw material.

[0032] Deprotonation (dehydrogenation) modification method: In a washable Buchner funnel, No. 41 filter paper is spread, 100 g of the above-mentioned polyaniline is added, and it is washed with 500 ml of distilled water to remove residual acid; then the powder on the filter paper is poured into a 4-liter glass reaction bottle with a stirrer, 2000 ml of 0.5M potassium hydroxide is added, and stirring is started for 45 minutes, and then the solution is filtered through a Buchner funnel (No. 41 filter paper), and the precipitate is washed with 800 ml of distilled water. The color of the polyaniline changes from dark blue-green to copper brown, and the deprotonated polyaniline of the present invention is obtained.

[0033] 2. Prepare a modified polyaniline solution; slowly add 50 g of deprotonated polyaniline into 300 ml of acetic acid solution and start stirring until the solution turns dark blue and completely dissolves.

[0034] 3. Prepare an anti-sticking agent; add 35g of the above polyaniline solution into a 2000ml beaker, add 100ml of distilled water, start stirring, and continue to add 8g of a film-forming agent (the film-forming agent is: polyvinyl alcohol with a degree of alcoholysis of 99.5-99.9 mole% and a degree of polymerization of 1350-1550, and the polyvinyl alcohol is prepared to have a solid content of 5.0%), stir for 1 hour, and then use 5.2g of 8% aqueous ammonium hydroxide solution to adjust the pH value to 12.8, continue to mix thoroughly, and test the viscosity of the aqueous solution to be 6.1mPa.s, and the anti-sticking agent of the present invention can be obtained.

[0035] The preparation method of the film-forming agent involved in the present application is as follows: 95.0 g of deionized water is added to a conventional glass bottle with a stirrer, and under stirring conditions, 5.0 g of polyvinyl alcohol solid powder with a degree of alcoholysis of more than 99.5% and a degree of polymerization of 1350-1550 is evenly added, soaked for 15 minutes, then heated to 90°C, continued to stir for 1 hour, and then cooled to below room temperature to prepare a 5.0% polyvinyl alcohol aqueous solution.

[0036] The anti-sticking agent of the present invention is a dark blue to black liquid with a certain viscosity and no insoluble matter. It does not react with the main and auxiliary dispersants of vinyl chloride suspension polymerization, anionic, cationic, nonionic and anionic and cationic surfactants, vinyl chloride monomer or other vinyl monomers, polar or non-polar solvents, alkalis, oils or greases. It is not limited by the above vinyl chloride polymerization, and the anti-sticking agent can be used in any reaction kettle of vinyl polymerization system to prevent scaling.

[0037] Application test of the anti-sticking agent of the present invention on the surface of the reactor; 1. Use a 2-liter glass reactor to simulate the acidic medium conditions in the presence of vinyl chloride to test the film-forming property of the material of the present invention. Completely simulate the suspension polymerization process of vinyl chloride, spray 15 ml of the anti-sticking agent (blue liquid) of the present invention with a solid content of 1.5% (calculated as modified polyaniline solution, obtained by dilution in Example 2) on the inner surface of a 2-liter glass reactor, let it stand for 5 minutes, form a film or layer of about 10 microns, and then flush it. Immediately inject 1.8 liters of distilled water into the reactor, heat it to 65°C, and adjust the pH value to 2.0-3.0 with 0.1N hydrochloric acid solution. Open the reactor and stir for 15 minutes, then pour the water into a transparent polyethylene container.

[0038] Observe whether the distilled water changes color. Prepare three samples of the present invention with different solid contents (obtained by dilution in Example 2) and test them according to the above test method. Each sample is sprayed on the inner wall of the reactor three times, and 50 ml of the sample is retained each time for spectrophotometric evaluation.

[0039] Analyses were performed using a Milton Roy Spectronic ZID spectrophotometer.

[0040] This example selects different concentrations of anti-sticking kettle as the following samples: 1. For blank No. 1, prepare distilled water with pH 2.2 using 0.1N HCl.

[0041] 2. Standard sample No. 2 is a sample with a solid content of 1.5%.

[0042] 3. Standard product No. 3 is a sample with a solid content of 2.5%.

[0043] 4. Standard product No. 4 is a sample with a solid content of 5.0%.

[0044] Spectrophotometer test results: After calibration of the instrument in parallel with Blank No. 1, the absorbance of the above samples was measured on a Milton Roy Spectronic ZID spectrophotometer.

[0045] 1. The absorbance of standard sample No. 2 is: 5.0525; 2. The absorbance of standard 3 sample is: 10.2362; 3. The absorbance of standard sample No. 4 is: 20.4702; The results were in line with the Beer-Lambert law (A=Kbc). Then, using the above spraying procedure, different solid content samples were sprayed in the reactor three times, 50 ml of sample was retained each time, and the absorbance of each sample was tested using a Milton Roy Spectronic ZID spectrophotometer.

[0046] Absorbance results: 1. All three tests of Standard No. 2 are: 2-ND 0.0; 2. All three tests of Standard 3 are: 3-ND 0.0; 3. All three tests of Standard 4 are: 4-ND 0.0; Results and Discussion: As the number of spraying increases from 1 to 3 times, the color of the coating on the inner wall of the reactor deepens and becomes a darker blue-green, indicating that the coating becomes thicker as the number of spraying increases. The above results show that all coating materials adhere to the inner wall of the reactor and form a coating film on the glass or stainless steel surface to protect the reactor from scaling.

[0047] The anti-sticking agent of the present invention is compared with a commercial anti-sticking agent (NOXOL WSW (made in Italy)) on the market: NOXOL WSW: Appearance: light yellow transparent liquid; Solid content: 5.5±0.5wt%; pH: 12.0-13.0; The same test method was used, but the anti-sticking agent was replaced with NOXOL WSW for comparison. Observe whether the distilled water changes color. NOXOL WSW samples with different solid contents of 1.5%, 2.5% and 5.0% were prepared. When diluted with water, the light yellow liquid turned blue, indicating that the product cannot be diluted with water. Therefore, the NOXOL WSW stock solution was taken for comparison test, and the test method remained unchanged. After the above test method was used, 50 ml of the above distilled water was taken as a sample and analyzed using a Milton Roy Spectronic ZID spectrophotometer.

[0048] Results and Discussion: For the sample of the present invention, as the number of spraying increases from 1 to 3 times, the color of the coating on the inner wall of the reactor deepens and becomes a darker blue-green color, indicating that the coating becomes thicker as the number of spraying increases. However, when the distilled water sample is tested, there is no color change when observed with the naked eye, which can be understood as the coating not falling off.

[0049] When the NOXOL WSW stock solution was used for the above test, the distilled water turned blue in the first test, and the distilled water was blue and darker in the second and third tests, indicating that only part of the NOXOL WSW was effective and part of the coating had fallen off. The above phenomenon is visible to the naked eye and does not require a spectrophotometer for analysis.

[0050] Similarly, the present application tested samples of Examples 1, 3, and 4, respectively, and the results were similar to those of Example 2, showing that all coating materials of the present invention adhered to the inner wall of the reactor, while only a portion of the coating of NOXOL WSW protected the inner wall of the reactor.

[0051] In summary, the anti-sticking agent of the present invention is sprayed onto the inner wall of the reactor, showing better film continuity, smoother and no peeling. As shown in the above description and examples, when the anti-sticking agent of the present invention is sprayed onto the surface of the reactor in contact with the reaction medium before the reactor is loaded, the accumulation of polymer can be significantly reduced, thereby improving productivity, reducing labor and maintenance costs, etc.

[0052] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An anti-sticking kettle agent, characterized in that The invention comprises the following components by weight: 1.5%-35% of modified polyaniline solution, 0.5%-8% of film-forming agent and the balance of water.

2. The anti-sticking kettle agent according to claim 1, characterized in that The modified polyaniline solution comprises modified polyaniline and a cosolvent; the mass content of the modified polyaniline solution is 10-40%.

3. The anti-sticking kettle agent according to claim 2, characterized in that The modified polyaniline is sulfonated polyaniline or deprotonated polypropylamine; The sulfonated polyaniline is obtained by sulfonating polyaniline; the molecular weight of the polyaniline is 80,000-150,000, y=0.35-0.7; the y value represents the degree of redox of the polyaniline; The deprotonated polyaniline is obtained by dehydrogenating polyaniline; the molecular weight of the polyaniline is 80,000-150,000, y=0; and the y value represents the redox degree of the polyaniline.

4. The anti-sticking kettle agent according to claim 3, characterized in that The sulfonated polyaniline is prepared by the following steps: adding polyaniline to a sulfonating agent, controlling the reaction temperature at 10-35°C, and reacting for 2-5 hours; the sulfonating agent is fuming sulfuric acid, a 98% or more sulfuric acid aqueous solution, or sulfur trioxide; The deprotonated polyaniline is prepared by the following steps: immersing polyaniline in an alkaline solution, mixing for 40-60 minutes, filtering to obtain a precipitate, and washing to obtain the deprotonated polyaniline.

5. The anti-sticking kettle agent according to claim 2, characterized in that The cosolvent is one of dimethyl sulfoxide, N-methyl-2-pyrrolidone, tetrahydrofuran, formic acid, acetic acid, or dimethylformamide or a mixture thereof.

6. The anti-sticking kettle agent according to claim 1, characterized in that Viscosity: 3.0-12.0mPa.s, pH ≥ 12.

0.

7. The anti-sticking kettle agent according to claim 1, characterized in that The solid content of the film-forming agent is 5% polyvinyl alcohol solution; the alcoholysis degree of the polyvinyl alcohol is 99.5-99.9 mole %, and the polymerization degree is 1350-1550.

8. A method for preparing the anti-sticking agent according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: adding deionized water into a mixing container, starting stirring, adding a modified polyaniline solution and a film-forming agent; then adding an alkali solution to adjust the pH to ≥ 12.0, and continuing to fully mix to obtain the anti-sticking kettle agent finished product.

9. Use of the anti-sticking agent according to any one of claims 1 to 7, characterized in that: Applied to vinyl polymerization reactor.

Citation Information

Patent Citations

  • Anti-thread-gluing and anti-corrosion thread coating and preparation method thereof

    CN117384535A

  • PROCESS FOR MANUFACTURING POLYANILINE OF HIGH MOLECULAR WEIGHT IN THE FORM OF EMERALDINE AND POLYANILINE OBTAINED BY THIS PROCESS

    FR2767138A1

  • Method for making polyaniline with high molecular mass in the form of emeraldine and polyniline obtained by said method

    US6265532B1